Improving prediction of recanalization in acute large‐vessel occlusive stroke. (June 2014) - Vanacker, P.; Lambrou, D.; Eskandari, A.; Maeder, P.; Meuli, R.; Ntaios, G.; Michel, P.
Summary Background Recanalization in acute ischemic stroke with large‐vessel occlusion is a potent indicator of good clinical outcome. Objective To identify easily available clinical and radiologic variables predicting recanalization at various occlusion sites. Methods All consecutive, acute stroke patients from the Acute STroke Registry and Analysis of Lausanne (2003–2011) who had a large‐vessel occlusion on computed tomographic angiography (CTA) (< 12 h) were included. Recanalization status was assessed at 24 h (range: 12–48 h) with CTA, magnetic resonance angiography, or ultrasonography. Complete and partial recanalization (corresponding to the modified Treatment in Cerebral Ischemia scale 2–3) were grouped together. Patients were categorized according to occlusion site and treatment modality. Results Among 439 patients, 51% (224) showed complete or partial recanalization. In multivariate analysis, recanalization of any occlusion site was most strongly associated with endovascular treatment, including bridging therapy (odds ratio [OR] 7.1, 95% confidence interval [CI] 2.2–23.2), and less so with intravenous thrombolysis (OR 1.6, 95% CI 1.0–2.6) and recanalization treatments performed beyond guidelines (OR 2.6, 95% CI 1.2–5.7). Clot location (large vs. intermediate) and tandem pathology (the combination of intracranial occlusion and symptomatic extracranial stenosis) were other variables discriminating between recanalizers and non‐recanalizers. For patients with intracranial occlusions, the variables significantly associated with recanalization after 24 h were: baseline National Institutes of Health Stroke Scale (NIHSS) (OR 1.04, 95% CI 1.02–1.1), Alberta Stroke Program Early CT Score (ASPECTS) on initial computed tomography (OR 1.2, 95% CI 1.1–1.3), and an altered level of consciousness (OR 0.2, 95% CI 0.1–0.5). Conclusions Acute endovascular treatment is the single most important factor promoting recanalization in acute ischemic stroke. The presence of extracranial vessel stenosis or occlusion decreases recanalization rates. In patients with intracranial occlusions, higher NIHSS score and ASPECTS and normal vigilance facilitate recanalization. Clinical use of these predictors could influence recanalization strategies in individual patients.